Clear-cutting disease control : capital-led deforestation, public health austerity, and vector-borne infection /: capital-led deforestation, public health austerity, and vector-borne infection. ([2018]) - Wallace, Rodrick; Chaves, Luis Fernando; Bergmann, Luke R; Ayres, Constńcia; Hogerwerf, Lenny; Kock, Richard; Wallace, Robert G
No abstract available